Alpine Skiing as Winter-Time High-Intensity Training - Stöggl, Thomas Leonhard; Schwarzl, Christoph; Müller, Edith E; Nagasaki, Masaru; Stöggl, Julia; Schönfelder, Martin; Niebauer, Josef (Medicine and science in sports and exercise, 2017)
To counteract the winter activity deficit, we set out to analyze cardiorespiratory and metabolic responses of two high-intensity training (HIT) protocols during alpine skiing (AS), cross-country skiing (XCS), and indoor cycling (IC) and the effects of sex, age, and fitness level in this comparison. Nineteen healthy subjects (two age and fitness groups, both sexes) performed AS, XCS, and IC with measurements of oxygen uptake (V˙O2), energy expenditure (EE), HR, lactate, blood glucose and rate of perceived exertion, determined during 4 min of continuous HIT (HITc: 90% HRmax for XCS and IC or short turn skiing during AS) or 10-min intermittent HIT [HITint: 5 × 1 min high intensity (>90% HRmax or short turn skiing), 1 min active recovery]. During all three exercise modes and irrespective of HIT protocols, sex, age, and fitness, participants were able to reach exercise intensities >90% HRmax and >84% V˙O2max. In all exercise modes 10-min of HITint with a 10-min postexercise O2 consumption phase resulted in greater mean EE per minute compared to 4-min HITc with 10 min postexercise O2 consumption. When applying the same HIT loading and recovery pattern to all three exercise modes, EE during approximately 1:15 h of AS was equivalent to about 1:00 h of either XCS or IC. Across all exercise modes and HIT protocols, high cardiorespiratory and metabolic responses were achieved regardless of age, sex, or fitness. EE during AS can be maximized by choosing the skiing mode "short turn skiing" in combination with an HITint to prolong the duration of continuous high-intensity loading during each descent. Therefore, all exercise modes and both HIT protocols are applicable and feasible in a broad spectrum of healthy subjects.